Kemampuan Mengenal Angka Menggunakan Media Wit Ongko pada Anak Usia Dini Kelompok A - Nurjannah, Siti; Trianggono, Mochammad Maulana (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Early childhood is an important phase for developing children's intelligence, including number recognition skills, which are the basis for further math learning. This study aims to improve the ability to recognize numbers 1-10 in children aged 4-5 years using wit ongko media in group A PAUD Darunnajah Tamansari. This research is a Classroom Action Research (PTK) with Kurt Lewin model. The subjects in this study were 15 children in group A. Data were collected using observation techniques and field notes, which refer to the ability to (a) count numbers 1-10, (b) show the order of objects 1-10, and (c) connect number symbols with objects. Data were analyzed using the percentage formula which is quantitative and qualitative. The results showed that the average ability of children in recognizing numbers in the pre-cycle for each indicator was (a) 63.25% (good), (b) 58.25% (sufficient), (c) 51.75% (poor); cycle I was (a) 66.67% (good), 58.33% (sufficient), 55% (sufficient); and cycle II was (a) 90% (very good), 88.25% (very good), 80% (very good). Thus, the use of wit ongko media is effective in improving the ability to recognize numbers in group A children at PAUD Darunnajah Tamansari.